Mapa jako narzędzie klasyfikacji danych w socjologii. Poza przestrzenną lokalizację wyobrażeń = Map as a data classification tool in sociology. Beyond spatial location of imaginativeness - Luczys, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
A map as a research tool, being the domain within/of environmental psychology, cognitive geography of the city, cognitive science, human geography, is also a conglomerate of evaluation and/or a source of patterns of perceiving the city within the examined communities, so valuable for a sociologist.
Keywords: mapa; socjologia